Live birth rate after oocyte donation in females diagnosed with turner syndrome: a systematic review and meta-analysis - Pegah Rashidian; Mohammadamin Parsaei; Shaghayegh Karami; Tayebe Sadat Sayafi Sharifi; Zahra Sadin; Seyyed Amirhossein Salehi (BMC, 2024)
Abstract Background An enduring challenge for women diagnosed with Turner syndrome (TS) is infertility. Oocyte donation (OD) offers a chance of pregnancy for these patients. However, current data on pregnancy outcomes are inadequate. Hence, this systematic review aims to explore the clinical outcomes of OD in patients with TS. Methods A systematic search was conducted in PubMed, Web of Sciences, Scopus, and Embase for relevant papers from 1 January 1990 to 30 November 2023. Our primary research objective is to determine the live birth rate among women with TS who have undergone in vitro fertilization (IVF) using OD for fertility purposes. Specifically, we aim to calculate the pooled live birth rates per patient and per embryo transfer (ET) cycle. For secondary outcomes, we have analyzed the rates of clinical pregnancy achievement per ET cycle and the incidence of gestational hypertensive complications per clinical pregnancy. Prevalence meta-analyses were performed using STATA 18.0 by utilizing a random-effects model and calculating the pooled rates of each outcome using a 95% confidence interval (CI). Results A total of 14 studies encompassing 417 patients were systematically reviewed. Except for one prospective clinical trial and one prospective cohort study, all other 12 studies had a retrospective cohort design. Our meta-analysis has yielded a pooled live birth rate per patient of 40% (95% CI: 29-51%; 14 studies included) and a pooled live birth rate per ET cycle of 17% (95% CI: 13-20%; 13 studies included). Also, the pooled clinical pregnancy achievement rate per ET cycle was estimated at 31% (95% CI: 25-36%; 12 studies included). Moreover, the pooled rate of pregnancy-induced hypertensive disorders per clinical pregnancy was estimated at 12% (95% CI: 1-31%; 8 studies included). No publication bias was found across all analyses. Conclusions This study demonstrated promising pregnancy outcomes for OD in patients with TS. Further studies are essential to address not only the preferred techniques, but also the psychological, ethical, and societal implications of these complex procedures for these vulnerable populations. Trial registration This systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the registration code CRD42023494273.